2014
DOI: 10.1021/ie402970v
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Study of Mixing Performance of High-Viscosity Fluid in Novel Static Mixers with Multitwisted Leaves

Abstract: The flow performance of a high-viscosity fluid in novel static mixers with multitwisted leaves was investigated numerically in the range of Re = 0.1−150. The effects of mixing-segment construction, Reynolds number, and aspect ratio on the chaotic mixing characteristics of different static mixers were evaluated based on the Lagrangian tracking method. The tracer particle distributions, G values, extensional efficiency characteristics, and stretching fields were used to evaluate the dispersion and distribution m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 34 publications
(72 reference statements)
1
26
0
Order By: Relevance
“…Consequently, the velocity field is likely to be well‐described if pressure results are satisfactory . The numerical pressure results of CFD models predicted by Meng et al had close agreement with the data available in previous literature . In order to guarantee that the CFD model of the Kenics static mixer correctly predicted its mixing behaviour over a broad range of laminar conditions, the model was also validated by comparing the predicted numerical residence time distribution (RTD) to experimental results in the literature, as shown in Figure b.…”
Section: Methodssupporting
confidence: 57%
“…Consequently, the velocity field is likely to be well‐described if pressure results are satisfactory . The numerical pressure results of CFD models predicted by Meng et al had close agreement with the data available in previous literature . In order to guarantee that the CFD model of the Kenics static mixer correctly predicted its mixing behaviour over a broad range of laminar conditions, the model was also validated by comparing the predicted numerical residence time distribution (RTD) to experimental results in the literature, as shown in Figure b.…”
Section: Methodssupporting
confidence: 57%
“…A quantitative comparison of industrial static mixers based on their performance revealed that open mixers compared with compact mixers require lower pressure drop to drive the flow, but at the expense of increasing mixing length 3 . Design modifications have also been performed to obtain usually a better and faster mixing 4‐7 . For example, Liu et al 5 used a frame‐indifferent parameter to classify the flow types in the SMX mixer and concluded that using a mixing element with 10 crossbars followed by the standard SMX mixer with eight crossbars gives the best mixing quality.…”
Section: Introductionmentioning
confidence: 99%
“…The mixing is ensured by stretching and reorientation of fluid during its passage through the blade: the twist and perpendicular cut delivers a sequence of folding and stacking (Rafiee et al, 2013). Meng et al (2014) studied numerically the mixing performance of static mixers with multi-twisted leaves like Kenics mixer. Meijer et al (2012) achieved a quantitative comparison of static mixers.…”
Section: Introductionmentioning
confidence: 99%